2016
DOI: 10.1039/c5cp06183k
|View full text |Cite
|
Sign up to set email alerts
|

Photon-absorbing charge-bridging states in organic bulk heterojunctions consisting of diketopyrrolopyrrole derivatives and PCBM

Abstract: We have investigated the photo- and electrochemical properties of five diketopyrrolopyrrole (DPP) derivatives both experimentally and theoretically. In the experimental study, we found that a blend of a DPP derivative named D2 and phenyl-C61-butyric acid methyl ester (PCBM) exhibits the highest internal quantum efficiency (IQE) and power convergence efficiency (PCE) among the five derivatives investigated. In the theoretical study, we found that the open-circuit voltage can be estimated from the difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…It can be seen that the EQE and JSC becomes larger as ∆Q, dCT, and ∆μD/A increase (in particular, the PTB7/PC71BM system is better than the PTBF2/PC71BM system). This agrees with the observation from [7,8] that ∆μD/A increases as the EQE increases. This comparative examination indeed indicates that ∆Q, dCT, and ∆μD/A rather than ∆μD are a good "descriptor" for assessing the donor quality contributing to solar cell performance.…”
Section: Theoretical Descriptorssupporting
confidence: 92%
See 2 more Smart Citations
“…It can be seen that the EQE and JSC becomes larger as ∆Q, dCT, and ∆μD/A increase (in particular, the PTB7/PC71BM system is better than the PTBF2/PC71BM system). This agrees with the observation from [7,8] that ∆μD/A increases as the EQE increases. This comparative examination indeed indicates that ∆Q, dCT, and ∆μD/A rather than ∆μD are a good "descriptor" for assessing the donor quality contributing to solar cell performance.…”
Section: Theoretical Descriptorssupporting
confidence: 92%
“…They showed that an internal dipole moment along the polymer chain is critical in maintaining the pseudo-charge-transfer characteristics comparing the PCEs of PBB3 and PTB7 copolymers, which have smaller and larger dipole moments, respectively; the latter have larger PCE and JSC compared with the former. On the other hand, we have confirmed by experiments and quantum chemistry calculations on the photophysical and electrochemical properties of complexes of diketopyrrolopyrrole-based donors and a PCBM acceptor that intermolecular charge transfer in the D/A complexes (∆μD/A) rather than ∆μD plays a crucial role in determining solar cell efficiency [8,9].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results suggest that electronic excitation of these dye–TiO 2 systems directly induces electron injection into the TiO 2 surface. Such excitations inducing direct charge transfer have been known to affect not only DSCs but also organic thin film solar cells …”
Section: Resultsmentioning
confidence: 99%
“…As showing Figure 1, the calculated λ abs value obtained at PBE0 (543 nm) level provided better agreement with the experimental value (523 nm) (Shiau et al, 2015) than those obtained with other levels of theory, with the deviation being 20 nm. Although B3LYP appeared adapted to 1,3,5-triazine and DPP derivatives in literature (Feng et al, 2014; Vala et al, 2014; Jin, 2015; Jin and Irfan, 2015; Jin and Xiao, 2015; Fujii et al, 2016), the λ abs value obtained at the B3LYP/6-31G (d,p) level is worsen accordance with the experimental data (the deviation is 48 nm) than that for at the PBE0/6-31G (d,p) level (the deviation is 20 nm). Additionally, we also calculated the FMOs energy levels of molecule 1 using both at PBE0 and B3LYP methods.…”
Section: Computational Detailsmentioning
confidence: 99%